Chinese Studies of Female Characters in Hardy's Novels: A Feminist Approach. Issue 3 (March 2016) - Ling, Bo
Abstract: Hardy's novels were characterized by a great variety of women. Since the introduction of Hardy to China, critics have considered his female characters from diverse perspectives and arrived at different and even contradictory conclusions. This paper aims to outline the landscape of Chinese studies of Hardy's women characters. Particular attention will be given to the three types of women Chinese critics identify in Hardy's novels. Since studies of women figures will inevitably cover issues which are major concerns of feminist criticism, this paper will also comment on these studies from a feminist perspective. Though these critics arrive at different conclusions and hold diverse views towards Hardy's female characters, their identification of three types of women captures the intrinsic pattern and logic behind Hardy's observation and presentation of women.